Identification of genes differentially expressed in breast cancer - Reis, Vânia Isabel Gonçalves Pereira dos (2013)
Breast cancer comprises heterogeneous tumors with different clinical characteristics, disease courses, and responses to specific treatments. Moreover, breast carcinomas result mainly from the accumulation of genetic and epigenetic alterations in epithelial cells of mammary gland. The identification of novel genes differentially expressed in breast cancer has important implications in understanding the molecular mechanisms underlying breast tumorigenesis, and developing new diagnostic and therapeutic targets. Therefore, the aim of this work was to identify genes differentially expressed in the breast cancer MCF7 cells, and to confirm its differential regulation in breast cancer. In this study, we used the suppressive subtractive hybridization technique to generate two subtractive libraries with 96 clones each, which were subsequently digested with EcoRI and then, all the plasmids with insert were sequenced. These results were further analyzed by Blast tool and GeneBank. We identify 36 genes as overexpressed and 19 genes as underexpressed in MCF7 cells. Some of these genes were previously identified as over- or underexpressed in breast cancer; however we found several genes that haven’t yet been described as up or down-regulated in MCF7 cell line. In the future, these novel genes may be used as possible biomarkers, diagnostic markers or therapeutic targets in breast cancer.